Implementation Of Entrepreneurial Spirit and Innovation Business Success Of Coffee Shops (Case Study Of Telos Kopi In Gunungsitoli City) - Harefa, Umi Kalsum; Zebua, Emanuel; Batee, Maria Magdalena; Baene, Eduar (ProBisnis : Jurnal Manajemen, 2024)
Telos Coffee is a coffee shop located in Gunungsitoli City, offering a variety of coffee blends and preparations that attract consumers and coffee enthusiasts. It has become a favorite spot for young people to gather, socialize, or work on office and university assignments. The purpose of this research is to understand the entrepreneurial spirit implementation by the owner of Telos Coffee in running the coffee shop business, the effective implementation of innovative practices by the owner, and the strategies employed by Telos Coffee to succeed in the coffee shop business in Gunungsitoli. This qualitative research adopts a case study approach, utilizing three variables and involving three informants. The findings reveal that Telos Coffee's entrepreneurial spirit is evident through increased customer numbers, diverse coffee bean and menu offerings, improved facilities, and a strategic location selection. The innovation implemented by Telos Coffee includes offering unique products, such as various coffee types from different regions of Indonesia, a focus on in-house coffee blends crafted by Telos Coffee's baristas, affordable pricing, actualizing a representative location, and enhancing supporting facilities and infrastructure. The success of Telos Coffee is attributed to various promotional programs on social media, effective communication with peers and organizations, and the establishment of a positive image among customers, positioning Telos Coffee favorably in the eyes of its clientele.